2015
DOI: 10.1007/s11010-015-2541-9
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of autophagic-proteolysis in C2C12 cells by saccharopine

Abstract: Muscle wasting impairs physical function and leads people to a bedridden state. We previously demonstrated that lysine (Lys) suppresses autophagic-proteolysis through the Akt pathway. However, the effect of metabolites of Lys on proteolysis is unclear. In this study, we investigated the effect of saccharopine (Sac), a metabolite of Lys, on proteolysis in C2C12 cells. When C2C12 myotubes were incubated in serum-free medium containing Sac, the rate of proteolysis, which was evaluated by 3-methylhistidine release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Opine dehydrogenases (OpDHs, E.C.1.5.1.28) are a class of AADHs that catalyse the reversible reductive coupling of amino acid and keto acids to form N ‐derivatised amino acids called opines. The model reaction catalysed by these enzymes in the BRENDA database (http://www.brenda-enzymes.org) is the NADH‐dependent coupling of aminopentanoic acid 15 and pyruvate 16 into (2 S )‐2‐{[1‐( R )‐carboxyethyl]amino}pentanoate 17 (Scheme ).…”
Section: Opine Dehydrogenases and Their In Vitro Evolution For The Rementioning
confidence: 99%
“…Opine dehydrogenases (OpDHs, E.C.1.5.1.28) are a class of AADHs that catalyse the reversible reductive coupling of amino acid and keto acids to form N ‐derivatised amino acids called opines. The model reaction catalysed by these enzymes in the BRENDA database (http://www.brenda-enzymes.org) is the NADH‐dependent coupling of aminopentanoic acid 15 and pyruvate 16 into (2 S )‐2‐{[1‐( R )‐carboxyethyl]amino}pentanoate 17 (Scheme ).…”
Section: Opine Dehydrogenases and Their In Vitro Evolution For The Rementioning
confidence: 99%
“…Lysine is catabolized in developing plant tissues through the saccharopine pathway, and have been shown to be involved in the development of maize seed and stress responses [53]. In the case of mammalian myotubes, saccharopine was shown to stimulate Akt and mTOR signalling that has suppressed autophagic-proteolysis, and might reduce muscle wasting [54].…”
Section: Hydroalcoholic Fenugreekmentioning
confidence: 99%
“…9,10) Lys is catabolized via the saccharopine (Sac) and pipecolic acid (Pip) pathways ( Fig. 1), 11) and Sac and Pip are catabolized to L-2aminoadipic acid (2-AA). 11) We previously showed that Sac, one of metabolites of Lys, suppresses autophagic proteolysis through a similar pathway as Lys.…”
mentioning
confidence: 99%
“…1), 11) and Sac and Pip are catabolized to L-2aminoadipic acid (2-AA). 11) We previously showed that Sac, one of metabolites of Lys, suppresses autophagic proteolysis through a similar pathway as Lys. 11) However, it is unknown whether other metabolites of Lys, Pip which is a major Lys metabolite produced in the Pip pathway and 2-AA which is a common metabolite in the Sac and Pip pathways, regulate protein turnover similarly to Sac.…”
mentioning
confidence: 99%